Performance and Fuel Consumption of Diesel Engine Fueled by Diesel Fuel and Waste Plastic Oil Blends: An Experimental Investigation - Priyo Adi Sesotyo; Eqwar Saputra; Agus Pulung Sasmito; Sunaryo Sunaryo (Automotive Experiences, 2021)
This study analyzes the performance of the diesel engine in terms of power, torque, specific fuel consumption, and thermal efficiency using diesel and pyrolysis oil. The waste plastic oil (WPO) used in this research was produced through a pyrolysis process using raw materials from Low-density Polyethylene (LDPE) mixed with diesel fuel in volume ratios WPO10, WPO20, WPO30, WPO40, and WPO50. In addition, a performance test was carried out on the single-cylinder diesel engine test bench. The results showed that performing the diesel engine with the addition of WPO increased the average power and torque by 5% and 3%, thereby producing a higher heating value. Furthermore, the concentration of WPO also reduces the level of specific fuel consumption to be more efficient, with a decrease in thermal efficiency. In conclusion, plastic waste pyrolysis oil is a promising alternative fuel applicable to a diesel engine.